PERANG SIBER di ERA KONEKTIVITAS TINGGI: KONVERGENSI JARINGAN KOMUNIKASI DATA dan KONFLIK DIGITAL - Rizky Habibie, Muhammad; Nabila, Putri; Zakiya Faizza, Aufa; Lil Alamin Arrasyid, Rakhmatan; Sulistyani, Anjar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the relationship between data communication network convergence and the escalation of global cyber warfare in the high-connectivity era. The integration of Internet of Things (IoT), cloud computing, edge computing, and 5G networks has created efficient yet vulnerable communication ecosystems. Using a qualitative comparative case study on SolarWinds (2020), Colonial Pipeline (2021), and Ukraine’s energy cyberattacks (2022–2024), the study finds that technological convergence expands cross-domain vulnerabilities (IT–OT–Cloud–Edge), triggers cascading impacts on critical systems, and accelerates the shift toward integrated digital warfare. The research introduces the Strategic Convergence Theory, emphasizing the need for zero-trust architectures, cross-sector cyber deterrence policies, and adaptive resilience-based governance to strengthen global cybersecurity.